In (a) Critical Condition: Reconsiderations of Krisis, Critique, and Theoria through Research Co-creation - Tschofen, Monique (Imaginations, 2024)
This paper explores the transformative potential of feminist research-creation through the lens of krisis and collaborative world-building, positioning research-creation as both a method and an ethic of care. Revisiting the ancient Greek concept of krisis—a moment of judgment and discernment—as a framework for inquiry, the author contrasts her prior scholarly work embedded in traditional frameworks of critique, often rooted in metaphors of violence, with the reparative methodologies developed through her work with the Decameron Collective. Over four years of iterative collaboration, the Collective produced award-winning multimodal digital projects Decameron 2.0 and Memory Eternal, which use storytelling, co-creation, and curation to respond creatively to crises from the pandemic to climate change. This paper argues that research co-creation can redefine krisis as a site of generative potential, where making and theorizing intertwine to produce new forms of knowledge and connection. By centering relationality, materiality, and feminist ethics, the Collective’s work moves beyond solitary modes of inquiry to establish a collaborative, care-driven practice. Situating research-creation within philosophical traditions of theoria and contemporary feminist thought, the paper highlights a number of ways such collaborative creation and curation can sustain communities, foster epistemological innovation, and offer reparative responses to crises. The paper ultimately positions research co-creation and co-authorship integrating storytelling, digital design, and collective reflection in slow scholarship as a vital methodology for navigating complex global challenges and reimagining the role of scholarship in a world facing ongoing crises.